Antifungal mechanism of carvacrol and osthole can disrupt cell structure integrity and interfere with energy metabolism in Neopestalotiopsis ellipsospora - Liu, Huifang; Yao, Jianmei; Yin, Rongxiu; Ma, Chiyu; Li, Lulu; Yang, Wen; Lei, Zhiwei (Frontiers in Sustainable Food Systems, 2025)
IntroductionTea gray blight disease is a major leaf disease in tea plants, significantly reducing tea quality and yield. Plants are rich in bioactive compounds that are safe, non-toxic, and biodegradable. In this study, we evaluated the antifungal activities and mechanisms of 11 plant extracts against N. ellipsospora.MethodsThis study evaluated the antifungal activity of 11 plant extracts against N. ellipsospora of tea gray blight disease and systematically examined the impacts of osthole and carvacrol on the mycelial morphology, mycelial weight, cell microstructure, membrane permeability, various biochemical substrate levels and related gene expression levels of N. ellipsospora.ResultsThe results showed that carvacrol and osthole exhibited significant antifungal effects among 11 plant extracts with EC50 values of 24.40 and 9.38 mg/L, respectively. Further research demonstrated that carvacrol and osthole significantly inhibited mycelial growth, reduced lesion areas on tea leaves, and markedly affected mycelial morphology and ultrastructure. Observations of mycelial morphology and ultrastructure revealed that carvacrol and osthole caused shrinkage and distortion of the mycelial surface, damage to cell wall and membrane, and disorganization of cellular organelles. Particularly carvacrol and osthole significantly increased chitinase activity, inhibited β-1,3-glucanase activity, and regulated the expression of genes encoding these enzymes.DiscussionThe findings indicated that carvacrol and osthole could inhibit the growth of N. ellipsospora by disrupting the integrity of the cell wall and membrane and interfere with energy metabolism. This study would provide a theoretical basis for the development of novel plant-based fungicides.